β-amyrin as an analgesic component of the leaves of Callistemon citrinus (Curtis) Skeels: Chemical, biological and in silico studies (Bangladesh Journal of Botany, 2019)
The analgesic potential of the leaves of Callistemon citrinus was reported earlier but no active principle for this analgesia was explored. To identify the major analgesic metabolite(s), the leaves were extracted with methanol and fractionated into petroleum ether, carbon tetrachloride, chloroform and aqueous soluble fractions. Based on the thin layer chromatography, the carbon tetrachloride fraction was subjected to gel permeation chromatography and a compound (1) was isolated, which was characterized as β-amyrin. Compound (1) displayed significant peripheral analgesia (p < 0.05) on mice model at an oral dose 200 mg/kg body weight. It also showed noticeable anti-inflammatory membrane stabilizing activity. In silico docking study of β-amyrin with cyclooxygenase (COX)-2 showed a good binding affinity (–9.1 Kcal/mol). Virtual pharmacokinetics and toxicity studies explore its potentials as a lead molecule having no extreme lethality.